A Model of an information system for the pharmacy unit : a case of Mbagathi district hospital - Ogara, Edwin Kojo Odhiambo (Strathmore University, 2012)
Mbagathi District Hospital (MDH) is a large Government institution in Nairobi Kenya. The researcher as a member of staff of the above mentioned institution's pharmacy department has a keen interest in improving its services and processes in totality. Most Government institutions are highly manual in their operations and this has resulted in a number of inefficiencies in service delivery. The researcher saw the need to address some of these inefficiencies with the advocacy for the implementation of an Information System (IS). The study sought to propose a model of an information system for pharmacy. It is to this end that the researcher intended to meet the objectives of this study namely: to identify the current challenges of the pharmacy information system; to demonstrate the effects of the current challenges of the information system for pharmacy; to review previous/existing models of an information system for pharmacy; to propose a suitable model for an information system for pharmacy; and to validate the proposed model for an information system for pharmacy. The researcher employed a cross¬sectional research design involving a simple stratified proportional sampling method through administering exit interview questionnaires to patients and staff. Descriptive statistics were used to analyse the collected data while cross tabulation was used to compare various variables against each other. Chi square (X2) test was done to test the existence of significant differences. In conclusion a model for information systems for pharmacy, whose components were informed by the research findings was proposed to have developed a specific model/guideline for an IS for pharmacy. The exact components and steps for implementation of an IS were developed and all in all, a backbone/baseline for a programmer to "take off' and develop software for pharmacy service delivery was set.
Keywords: Hospital pharmacy services--Kenya; Health System pharmacy